Effect of graphical method for solving mathematical programming problem (Daffodil International University Journal of Science and Technology, 2010)
In this paper, a computer implementation on the effect of graphical method for solving mathematical programming problem using MATLAB programming has been developed. To take any decision, for programming problems we use most modern scientific method based on computer implementation. Here it has been shown that by graphical method using MATLAB programming from all kinds of programming problem, we can determine a particular plan of action from amongst several alternatives in very short time. Keywords: Mathematical programming, objective function, feasible-region, constraints, optimal solution. DOI: 10.3329/diujst.v5i1.4379 Daffodil International University Journal of Science and Technology Vol.5(1) 2010 pp.29-36